Keterampilan Guru Mengelola Kelas dalam Meningkatkan Prestasi Belajar Siswa Kelas VI Bidang Studi Qur’an Hadits di MI NW Korleko - Masjudin Masjudin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This research aims to find out how teachers' classroom management skills improve student learning achievement. Various problems in the learning process are part of various unfinished studies discussed in various seminars, discussions and other academic activities to find various alternative solutions to problems faced by teachers in carrying out their duties as teachers and educators in school or madrasah environments.  The research method uses qualitative research and data is collected using interview, observation and documentation methods to secure the research objects in the field. The research was carried out at Madrasah Ibtida'iyah NW Korleko. The results of the research show that the classroom management carried out at the research location takes the form of classroom management skills when studying the field of Qur'an Hadith studies, namely classroom arrangement, teaching facility arrangement, student management, student management outside the classroom and classroom administration. Meanwhile, student learning achievement is still less successful because class management skills have not been implemented optimally, so there needs to be an increase in the teacher's class management skills so that student learning achievement can be even better